Families of Graceful Spiders with (2k+1)k, (2k+1)k+1 and (2k+1)+k+1 Legs - Berrocal Huamani, Nelson (2025)
We say that a tree is a spider if has at most one vertex of degree greater than two. We obtain existence of families of gracefuls spiders with ℓ(2k +1)−k, ℓ(2k +1)−k +1 and ℓ(2k +1)+k +1 legs. We provide specific labels for each spider graph, these labels are constructed from graceful path graphs that have a particular label, so there is acorrespondence between some paths and graceful spiders that we are studying, this correspondence is described in an algorithm outlined in the preliminaries.